The manifold beauty of Genesis one: a multi-layered approach - Davidson, Gregg R. (Kregel Academic, 2021)
Intro -- Title Page -- Copyright -- About the Authors -- Dedication -- Contents -- Acknowledgments -- Introduction: The Many Layers of Genesis 1 -- A Model Approach: What Can Be Learned from a Genealogy? -- Layer 1: Song -- Layer 2: Analogy -- Layer 3: Polemic -- Layer 4: Covenant -- Layer 5: Temple -- Layer 6: Calendar -- Layer 7: Land -- Conclusion -- Appendix 1: An Unbroken Covenant with Nature -- Appendix 2: Excerpts from Ancient Near East Origin Myths -- Bibliography.